التنوع المورفولوجي لنوعي التوت الأبيضMorus alba L.) ) والأسود (Morus nigra L.) لبعض المواقع في محافظة طرطوس (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2017)
نُفذ البحث خلال العامين 2014 و2015 في محافظة طرطوس لحصر بعض طرز نوعي التوتMorus alba وMorus nigra في ستة مواقع متفاوتة في ارتفاعها عن سطح البحر (0 - 500م)، إذ تم تحديد 33 طرازاً (22 من النوع الأبيض و11 من النوع الأسود) لتوصيفها مورفولوجياً وفينولوجياً وتحديد درجة القرابة المورفولوجية بينها إضافةً لوضع مفاتيح تصنيفية خاصة بها.أُجري التحليل العنقودي للطرز مجتمعةً بناءاً على 14 صفة مورفولوجية (أوراق، نورات زهرية، ثمار) إضافةً للتحليل العنقودي لكل من طرز النوع الأبيض والنوع الأسود على حدا؛ إذ أظهرت شجرة القرابة المورفولوجية للطرز مجتمعة وجود مجموعتين مستقلتين بنسبة تباين وصلت لـ 48%، ضمت المجموعة الأولى ثلاثة طرز تابعة للنوع الأسود والثانية 30 طرازاً تابعاً للنوعين معاً تراوحت نسبة التباين بينها من 0-38%، بينما أظهرت شجرة القرابة المورفولوجية لطرز التوت الأسود نسبة تباين وصلت لـ 47% مقارنة بـ 33% لطرز النوع الأبيض.إن درجة التشابه المورفولوجي متباينة بين الطرز المدروسة بغض النظر عن لون الثمار، ونسبة التباين ضمن طرز التوت الأسود أعلى منها ضمن طرز التوت الأبيض. This research was conducted during the period of 2014 - 2015 in six locations ranging from a height of between (0-500 m) in Syria, Tartous Governate in order to survey and evaluate some mulberry types belong to (Morus alba and Morus nigra). 33 types (22 of white mulberry and 11 of black mulberry) were determined for the purpose of morphological and phenological characterization and for the determination of the degree of morphological relationship between those types in addition to setting their own taxonomic keys. Morphological analysis was done based on 14 morphology characteristics (leaves, catkins, fruits) in addition to a cluster analysis for all types belongs to white and black species and for each species alone.The morphological tree for all types showed two main groups with a contrast ratio of (48%), the first group included three types belong to black mulberry, and the second group included 30 types belong to both species with a contrast ratio of (0-38%), while the morphological tree for the black species types showed a contrast ratio of (47%) and (33%) for the white specie types.The degree of morphological similarity is variable between the studied types regardless of fruits color, and the percentage of contrast among the black mulberry types is higher than white mulberry types.